2021
DOI: 10.1094/pdis-07-19-1398-pdn
|View full text |Cite
|
Sign up to set email alerts
|

First Report of Sugarcane Streak Mosaic Virus Infecting Sugarcane in Côte d’Ivoire

Abstract: Sugarcane streak mosaic virus (SCSMV; Poaceavirus; Potiviridae) is the causal agent of streak mosaic disease of sugarcane (Saccharum interspecific hybrids), a major industrial crop that is widely cultivated in tropical and subtropical regions for sugar and ethanol production. was first reported by Hall et al. (1998) from quarantined germplasm material exhibiting mosaic symptoms imported from Pakistan into the USA. Subsequently, the virus was also reported to occur in most of the Asian countries like Bangladesh… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

0
6
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
6
3

Relationship

0
9

Authors

Journals

citations
Cited by 12 publications
(6 citation statements)
references
References 9 publications
0
6
0
Order By: Relevance
“…Diagnosis of symptomatic samples identified five species of fungi, namely Colletotrichum sp, Lasiodiplodia sp, Pestalotia sp, Curvularia sp and Alternaria sp. According to several authors the fungal genera identified are responsible for cashew tree diseases in different producing countries [26] [27] [28]. They are said to be capable of attacking all cashew organs.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Diagnosis of symptomatic samples identified five species of fungi, namely Colletotrichum sp, Lasiodiplodia sp, Pestalotia sp, Curvularia sp and Alternaria sp. According to several authors the fungal genera identified are responsible for cashew tree diseases in different producing countries [26] [27] [28]. They are said to be capable of attacking all cashew organs.…”
Section: Discussionmentioning
confidence: 99%
“…They are said to be capable of attacking all cashew organs. In Côte d'Ivoire, C. gloeosporioides has been identified as responsible for anthracnose on all cashew organs [26]. The species L. theobromae, is involved in the drying of cashew buds bitten by helopeltis sp in Côte d'Ivoire [27].…”
Section: Discussionmentioning
confidence: 99%
“…SCSMV can be transmitted mechanically or through stem cuttings over long distances, and no insect vector has been found to transmit SCSMV [ 3 ]. A high incidence of SCSMV has been reported in sugarcane-producing areas such as China, India, Thailand, and Indonesia [ 3 , 6 , 7 , 8 ] and has also been reported in Iran and Africa [ 9 , 10 ]. Currently, the management of SCSMV involves growing virus-free planting materials and disease-resistant sugarcane varieties [ 11 ].…”
Section: Introductionmentioning
confidence: 99%
“…hybrid by MaYMV was found in sugarcane mosaic samples in China [7,8] and in India [9]. SCSMV is distributed in Asian countries [12] and was recently reported in Côte d'Ivoire [29].…”
Section: Introductionmentioning
confidence: 99%